2014
DOI: 10.1161/circep.113.000882
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Mapping of Ventricular Scar

Abstract: Background-Surviving myocytes within scar may form channels that support ventricular tachycardia (VT) circuits. There are little data on the properties of channels that comprise VT circuits and those that are non-VT supporting channels. Methods and Results-In 22 patients with ischemic cardiomyopathy and VT, high-density mapping was performed with the PentaRay catheter and Ensite NavX system during sinus rhythm. A channel was defined as a series of matching pacemaps with a stimulus (S) to QRS time of ≥40 ms. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…Entrainment mapping is the yardstick to characterize reentrant arrhythmias, but overestimation and underestimation of true isthmus length can cloud its conclusive performance similar to pace mapping. 38 Nevertheless, for unstable VTs, pace mapping is the best surrogate to approximate central anatomically protected segments, 5,13 and an ultra-high-density pace mapping from small closely spaced bipoles with rigorous matching criteria as was applied in our study reduces underestimation or overestimation of the central isthmus. Despite pace mapping at slower rates, which can reduce the likelihood of lines of functional block, pace map locations matching one of the induced VT morphologies with very long S-QRS intervals were identified in most patients, inclusive for fast VTs, signifying that functional latencies likely had a limited influence on the QRS morphology in the majority of VTs, and not just the exit sites but locations central within a VT channel were established.…”
Section: Study Limitationsmentioning
confidence: 91%
See 3 more Smart Citations
“…Entrainment mapping is the yardstick to characterize reentrant arrhythmias, but overestimation and underestimation of true isthmus length can cloud its conclusive performance similar to pace mapping. 38 Nevertheless, for unstable VTs, pace mapping is the best surrogate to approximate central anatomically protected segments, 5,13 and an ultra-high-density pace mapping from small closely spaced bipoles with rigorous matching criteria as was applied in our study reduces underestimation or overestimation of the central isthmus. Despite pace mapping at slower rates, which can reduce the likelihood of lines of functional block, pace map locations matching one of the induced VT morphologies with very long S-QRS intervals were identified in most patients, inclusive for fast VTs, signifying that functional latencies likely had a limited influence on the QRS morphology in the majority of VTs, and not just the exit sites but locations central within a VT channel were established.…”
Section: Study Limitationsmentioning
confidence: 91%
“…In our recent study, we showed that VT supporting channels have longer protected segments and slower conduction than channels that do not support VT. 13 The complex electrograms expressed from unprotected branched channel segments within the scar have broader voltage distribution compared with electrograms from relatively longer protected channels with paucity of side branches. 18 On the basis of these, we reasoned that the electric information pertinent to the framework of critical segments of VT channels is reflected in their activation time and voltage distribution (=entropy) patterns.…”
Section: See Editorial By Peters and Ciacciomentioning
confidence: 99%
See 2 more Smart Citations
“…Entrance site pacing, however, will frequently yield a "nonmatched" QRS as the stimulus wave front may also exit antidromically in a different manner from the VT. 47 Recently, it has been recognised that an abrupt transition between a paced-QRS that matches the clinical VT (exit site) and a non-matched paced-QRS (entrance site) can identify an isthmus. 48 Typical isthmus sites are located in areas with low EGM voltages (< 1.5 mV EGM), with dimensions ranging from 21-59 mm length by 15-47 mm width.…”
Section: Pace Mappingmentioning
confidence: 99%